(untitled) (Shiksha Shastra Saurabh, 2025)
The study examines the connection between higher education and economic growth of Nepal over the period (1990-2024) using time series data techniques with an ARDL bounds test co-integration approach. It’s outcomes (short-run and long-run) coefficients demonstrate that higher education has a highly significant and positive influence on economic growth in the country. The outcomes imply that investment in higher education plays a role of major contributor for poverty alleviation and fostering the sustainable economic growth in Nepal. The study also found that investment and government expenditure variables positively affect Nepalese economic growth performance. Conversely, inflation demonstrates a negative relationship with economic growth, though its impact is statistically significant at 1%. The empirical outcomes concluded that investing in higher education can boost the Nepalese economy and increasing the sustainable economic growth in Nepal.